Highest concentration of breast‐milk‐derived exosomes in colostrum. Issue 1 (12th November 2022) - Ohta, Motoki; Koshida, Shigeki; Jimbo, Itsuki; Oda, Machi; Inoue, Ryo; Tsukahara, Takamitsu; Terahara, Masaki; Nakamura, Yoshitaka; Maruo, Yoshihiro
Abstract: Background: Exosomes are nanosized extracellular vesicles, that play important roles in intercellular immune regulation. They have potential therapeutic utility for neonatal diseases including necrotizing enterocolitis. Breast‐milk‐derived exosomes have recently shown beneficial effects on intestinal damage in vitro and in vivo. However, the chronological change in breast‐milk‐derived exosome concentrations after delivery are unclear. Methods: In this prospective study, we enrolled 17 mothers who delivered premature infants admitted to a neonatal intensive care unit in Japan. We measured the consecutive concentrations of breast‐milk‐derived exosomes in the mothers for 48 weeks after delivery. Results: The median concentration of breast‐milk‐derived exosomes was 1.62 × 10 8 particles/ml in colostrum, showing a significant decrease after 2 weeks ( P  < 0.01). There was no association between the exosome concentration in colostrum and maternal perinatal factors including parity, mode of delivery, maternal age, and gestational age at delivery. Conclusions: We concluded that breast‐milk‐derived exosomes were the richest in colostrum. Our basic data regarding breast‐milk‐derived exosomes are expected to aid in the clinical application of exosomes for treating neonatal diseases.